Pengaruh penambahan zeolit alam termodifikasi sebagai media imobilisasi bakteri terhadap dekompisisi material organik secara anaerob - Melly Mellyanawaty; Chandra Wahyu Purnomo; Wiratni Budhijanto (Jurnal Rekayasa Proses, 2017)
This study aims to determine the effect of modified natural zeolite as microbial immobilization medium for anaerobic decomposition of organic materials. The modification was Fe2+ impregnation into the ring-shaped zeolite. Three different concentrations of Fe2+ solution were used to impregnate the zeolite, i.e. 10 mg/L, 100 mg/L and 2000 mg/L. The wet impregnation process was conducted. Four variations of Fe2+ concentration deposited into zeolite were prepared, i.e. 0 mgFe2+/gZeo (as control), 0.0016 mgFe2+/gZeo, 0.0156 mgFe2+/gZeo and 0.3125 mgFe2+/gZeo. The modified zeolite was added to the batch anaerobic reactor, which filled with the volume ratio of liquid substrate and zeolite of 1:1 for all variations of media. Distillery spent wash was used as the substrate in this study. The soluble Chemical Oxygen Demand (sCOD) value of the substrate was homogenized at 10000 mg/L. Effluent digester of cow manure bio digester was added as inoculum. The volume ratio of distillery spent wash to the inoculum was 2:1. The anaerobic process was conducted for 28 days.The performance of four media in the anaerobic digestion of distillation spent wash was measured in terms of sCOD, total solid (TS), and volatile solid (VS). The comparison among media was more accurately and conclusively represented by sCOD value. The visual analysis of sCOD trend during 28 days indicated that zeolite with 0.0156 mgFe/gZeo resulted in the highest sCOD removal of 66.73%. Meanwhile, zeolite with 0.3125 mgFe/gZeo increased the production of biogas by the highest percentage of 43% to be compared to control. Generally speaking, the addition of Fe2+ into zeolit led to higher removal of sCOD and produced more biogas than control.